Iron-based bimetallic catalyst as well as preparation method and use method thereof

By supporting the iron-based bimetallic catalysts prepared by zirconium-based and iron-based organic frameworks on zirconia, the problems of limited monometallic activity and limitations of bimetallic catalyst preparation methods are solved, and efficient carbon dioxide hydrogenation reaction is achieved to generate low-carbon olefins.

CN119565609AActive Publication Date: 2025-03-07EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202410949591.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2025-03-07
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

In the prior art, individual active metals such as iron have limited activity for carbon dioxide hydrogenation reaction, resulting in unsatisfactory carbon dioxide conversion, and the preparation method of Fe-based bimetallic catalysts has limitations in regulating the interaction and distribution between metals.

Method used

An iron-based bimetallic catalyst supported on zirconium oxide (ZrO2) is designed, which comprises a zirconium-based organic framework and an iron-based organic framework, and is prepared by calcining and soaking steps to form a uniformly distributed iron-based bimetallic oxide hybrid structure.

Benefits of technology

The catalyst exhibits high reaction activity and stability in the carbon dioxide hydrogenation reaction, the CO2 conversion rate can reach 44.6%, the selectivity of low-carbon olefins can reach 45%, and the preparation method is simple, low cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565609A_ABST
    Figure CN119565609A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based bimetallic catalyst as well as a preparation method and a use method thereof. The iron-based bimetallic catalyst comprises an active metal; the composite carrier comprises zirconium oxide, a zirconium-based organic framework and an iron-based organic framework, the zirconium-based organic framework is coated with the iron-based organic framework, and iron and the active metal are loaded on the zirconium oxide. The preparation method comprises the following steps: mixing zirconium nitrate pentahydrate and a first organic ligand for reaction to obtain a zirconium-based organic framework material; mixing the zirconium-based organic framework material, a second organic ligand and a metal salt for reaction to prepare a composite organic framework material; calcining the composite organic framework material, and soaking the calcined composite organic framework material in a metal salt solution; and carrying out drying treatment to obtain the iron-based bimetallic catalyst. The iron-based bimetallic catalyst is used for the catalytic reaction of carbon dioxide hydrogenation to generate low-carbon olefins.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an iron-based bimetallic catalyst and a preparation method and a use method thereof, and in particular to an iron-based bimetallic catalyst that can be used for a hydrogenation reaction of carbon dioxide, a preparation method of the iron-based bimetallic catalyst, and a use method of using the iron-based bimetallic catalyst for a catalytic reaction of carbon dioxide hydrogenation. Background Art

[0002] With the accelerated development of the industrial process, the combustion of large amounts of fossil fuels has led to a sharp increase in carbon dioxide (CO2) emissions, bringing about environmental problems such as the greenhouse effect and ocean acidification. Carbon dioxide is currently considered to be the main anthropogenic greenhouse gas, so carbon is often used to refer to greenhouse gases in the neutralization or net zero emission targets determined by various countries. Converting carbon dioxide into useful chemicals such as olefins, aromatics, and methanol through catalytic hydrogenation has been regarded as a cutting-edge direction for solving these problems. This method can not only effectively reduce carbon dioxide emissions, but also provide new economic value for carbon dioxide. Among them, low-carbon olefins (C2 = -C4 = ) is of particular interest because of its important role in synthetic plastics, polymers and other chemical products.

[0003] Since the activity of a single active metal, such as iron (Fe), for CO2 hydrogenation is limited, the CO2 conversion rate is not ideal. Similar to Fe, active metals such as cobalt (Co) and nickel (Ni) are also often used in CO2 hydrogenation because of their activity for CO2 hydrogenation. In recent years, in the research on Fe-based bimetallic catalysts, most of the preparation methods use impregnation or coprecipitation methods, which have certain limitations in regulating the interaction between Fe and the second active metal, metal distribution and composition control. Therefore, designing a reasonable and controllable Fe-based bimetallic catalyst is of great significance for further improving its catalytic performance.

[0004] Therefore, it is necessary to provide an iron-based bimetallic catalyst and a preparation method and a use method thereof, wherein the iron-based bimetallic catalyst can be used to synthesize light olefins through a hydrogenation reaction of carbon dioxide to solve the problems existing in the prior art. Summary of the invention

[0005] The main purpose of the present invention is to provide an iron-based bimetallic catalyst. The iron-based bimetallic catalyst embeds two different metal ions in its skeleton structure, thereby generating more catalytic active sites and adsorption sites, so that the structural adjustability can be further improved, and more superior physical and chemical properties are obtained. At the same time, the iron-based bimetallic supported on zirconium oxide (ZrO2) is evenly distributed, and the iron-based bimetallic catalyst has a regular surface morphology and uniform size under electron microscope TEM observation.

[0006] Another object of the present invention is to provide a preparation method and a use method of the above-mentioned iron-based bimetallic catalyst. The preparation method of the iron-based bimetallic catalyst is simple, does not contain precious metals, is suitable for large-scale preparation, has low cost and is environmentally friendly. The iron-based bimetallic catalyst has high reactivity and good stability in the reaction of preparing light olefins by catalytic hydrogenation of carbon dioxide, and the carbon dioxide conversion rate can reach 44.6%, and the light olefin selectivity can reach 45%.

[0007] To achieve the above-mentioned purpose, one embodiment of the present invention provides an iron-based bimetallic catalyst, which comprises: an active metal; and a composite carrier, the composite carrier comprising zirconium oxide (ZrO2), a zirconium-based organic framework and an iron-based organic framework; wherein: the iron-based organic framework is coated with the zirconium-based organic framework, and the iron of the iron-based organic framework and the active metal are loaded on the zirconium oxide.

[0008] In one embodiment of the present invention, the zirconium-based organic framework comprises a first organic ligand portion, and the first organic ligand portion is selected from at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin.

[0009] In one embodiment of the present invention, the iron-based organic framework comprises a second organic ligand portion, and the second organic ligand portion is selected from at least one of 2-aminoterephthalic acid, fumaric acid, and trimerephthalic acid.

[0010] In one embodiment of the present invention, the active metal is selected from at least one of cobalt (Co), nickel (Ni), manganese (Mn) and molybdenum (Mo).

[0011] In one embodiment of the present invention, the molar ratio of iron to the active metal is 10:1 to 1:2.

[0012] Another embodiment of the present invention provides a method for preparing an iron-based bimetallic catalyst, the preparation method comprising the following steps:

[0013] Step (S1): mixing zirconium nitrate pentahydrate and a first organic ligand in a first solvent to react and obtain a zirconium-based organic framework material;

[0014] Step (S2): mixing the zirconium-based organic framework material, a second organic ligand and a metal salt in a second solvent, wherein the metal salt comprises an iron salt and an active metal salt, to prepare a composite organic framework material;

[0015] Step (S3): calcining the composite organic framework material;

[0016] Step (S4): soaking the calcined composite organic framework material in a metal salt solution; and

[0017] Step (S5): Drying the solid portion of step (S4) to obtain the iron-based bimetallic catalyst as described above.

[0018] In one embodiment of the present invention, the first organic ligand is selected from at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin, and the second organic ligand is selected from at least one of 2-aminoterephthalic acid, fumaric acid and trimerephthalic acid.

[0019] In one embodiment of the present invention, in step (S1), the molar ratio of the zirconium nitrate pentahydrate to the first organic ligand is 1:1.

[0020] In one embodiment of the present invention, in step (S1), the reaction temperature is 80 to 120° C., and the reaction time is 10 to 48 hours.

[0021] In one embodiment of the present invention, in step (S2), the mass ratio of the zirconium-based organic framework material, the second organic ligand, and the metal salt is 2.1-3.3:0.8-1.2:2.7-3.5.

[0022] In one embodiment of the present invention, in step (S2), the iron salt is at least one of ferric nitrate, ferric acetate, ferric oxalate, ferric chloride and ferrous chloride; and the active metal salt is at least one of nickel nitrate, cobalt nitrate, manganese nitrate and ammonium molybdate.

[0023] In one embodiment of the present invention, in step (S2), the molar ratio of the iron salt to the active metal salt is 10:1 to 1:2.

[0024] In one embodiment of the present invention, in step (S3), the calcination temperature is 400 to 900° C., and the calcination time is 1 to 10 hours.

[0025] In one embodiment of the present invention, in step (S4), the auxiliary metal salt solution is formed by dissolving an auxiliary metal salt in deionized water, the auxiliary metal salt is at least one of sodium nitrate, sodium carbonate, sodium bicarbonate, potassium nitrate, potassium carbonate and potassium bicarbonate, and the mass ratio of the auxiliary metal salt to deionized water is (1.1-4.1):120; the soaking temperature is 20 to 80°C, and the soaking time is 2 to 6 hours.

[0026] In one embodiment of the present invention, in the step (S5), the drying process is carried out at a temperature of 80 to 120°C and for a time of 7 to 9 hours.

[0027] Another embodiment of the present invention provides a method for using an iron-based bimetallic catalyst, which comprises using the iron-based bimetallic catalyst to carry out a catalytic reaction of carbon dioxide hydrogenation in a fixed bed microreactor to produce light olefins; the conditions of the catalytic reaction of carbon dioxide hydrogenation are as follows:

[0028] The temperature is 200 to 500° C., the pressure is 3 MPa, the reaction raw materials contain hydrogen / carbon dioxide in a volume ratio of 2 to 4, and the space velocity is 2000 to 15000 ml / g per hour.

[0029] Beneficial effects of the present invention:

[0030] (1) The present invention first synthesizes a zirconium-based organic framework material, then grows an iron-based organic framework material by internal expansion to prepare a composite structure containing the zirconium-based organic framework material and the iron-based organic framework material, and finally prepares a hybrid structure of an iron-based bimetallic oxide supported on ZrO2 by calcination. The iron-based bimetallic catalyst prepared by the method of the present invention has the advantages of regular morphology and uniform size; the iron-based bimetallic particles supported on ZrO2 are uniformly distributed.

[0031] (2) The bimetallic compounds used in the present invention have a synergistic effect. The active metal can enhance the adsorption of CO2 and improve the dispersion of the active iron metal, thereby improving the reaction activity and life of the catalyst.

[0032] (3) The material structure of the iron-based bimetallic catalyst loaded on ZrO2 designed by the present invention can achieve a CO2 conversion rate of 44.6% and a low-carbon olefin selectivity of 45% for CO2 hydrogenation reaction. The preparation method is simple, the preparation conditions are also easy to control, and it does not contain precious metals, which has potential industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flowchart of a method for preparing an iron-based bimetallic catalyst according to an embodiment of the present invention.

[0034] Figure 2 This is an X-ray diffractometer (XRD) diagram of the iron-based bimetallic catalyst FeCo@ZrO2 prepared in Example 1 of the present invention.

[0035] Figure 3 This is a transmission electron microscope (TEM) image of the iron-based bimetallic catalyst FeCo@1.5ZrO2 prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the preferred embodiments of the present invention will be specifically cited below, and the accompanying drawings will be described in detail as follows. Furthermore, the singular forms "one", "an" and "said" mentioned in the present invention include plural references unless the context clearly stipulates otherwise. Numerical ranges (such as A of 10% to 11%) include upper and lower limits (i.e. 10%≦A≦11%) if there is no specific description; if the numerical range does not define the lower limit (such as B below 0.2%, or B below 0.2%), it means that the lower limit may be 0 (i.e. 0%≦B≦0.2%). The above terms are used to illustrate and understand the present invention, not to limit the present invention.

[0037] The "room temperature" of the present invention refers to 15 to 30°C, preferably 20 to 25°C.

[0038] The "normal pressure" in the present invention refers to 0.1 MPa.

[0039] If not otherwise specified, deionized water is generally used as the immersion or soaking solvent in the present invention.

[0040] Unless otherwise specified, all reagents and solvents used in the examples of the present invention are of analytical grade (AR).

[0041] Unless otherwise defined, all professional and scientific terms used in the context of the present invention have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.

[0042] One embodiment of the present invention provides an iron-based bimetallic catalyst, which mainly includes an active metal; and a composite carrier, wherein the composite carrier includes zirconium oxide (ZrO2), a zirconium-based organic framework and an iron-based organic framework, wherein the iron-based organic framework covers the zirconium-based organic framework, and the iron contained in the iron-based organic framework and the active metal are both loaded on the zirconium oxide.

[0043] In one embodiment, the zirconium-based organic framework comprises a first organic ligand portion. The first organic ligand portion is derived from a first organic ligand, and the first organic ligand can be at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin. Preferably, the first organic ligand is terephthalic acid.

[0044] In one embodiment, the iron-based organic framework comprises a second organic ligand portion, the second organic ligand portion is derived from a second organic ligand, and the second organic ligand can be at least one of 2-aminoterephthalic acid, fumaric acid, and trimerephthalic acid. Preferably, the second organic ligand is 2-aminoterephthalic acid.

[0045] In one embodiment, the active metal may be at least one of cobalt (Co), nickel (Ni), manganese (Mn) and molybdenum (Mo), and the active metal may exist in the form of a metal oxide. In one embodiment of the present invention, the molar ratio of iron in the iron-based organic framework to the active metal is 10:1 to 1:2, and may be, for example, 10:1, 5:1, 2:1, 1:2, but is not limited thereto, and may also be any other integer or non-integer value between 10:1 and 1:2. Preferably, the molar ratio of iron to the active metal is 10:1 or 5:1.

[0046] Another embodiment of the present invention provides a method for preparing an iron-based bimetallic catalyst, which mainly comprises the following steps: (S1) mixing zirconium nitrate pentahydrate and a first organic ligand in a first solvent for reaction to obtain a zirconium-based organic framework material; (S2) mixing the zirconium-based organic framework material, a second organic ligand and a metal salt in a second solvent to prepare a composite organic framework material; (S3) calcining the composite organic framework material; (S4) soaking the calcined composite organic framework material in a co-metal salt solution; and (S5) drying the solid portion of step (S4) to obtain the iron-based bimetallic catalyst as described above.

[0047] The present invention will describe the implementation details and principles of each of the above steps in detail below.

[0048] Please refer to Figure 1 As shown, the preparation method of the iron-based bimetallic catalyst of one embodiment of the present invention is first: (S1) mixing zirconium nitrate pentahydrate and a first organic ligand in a first solvent to react to obtain a zirconium-based organic framework material. In this step, the molar ratio of the zirconium nitrate pentahydrate and the first organic ligand can be 1:1, that is, an equimolar ratio. In one embodiment, the first solvent can be, for example, a mixed solvent of N,N-dimethylformamide (DMF) and formic acid in a volume ratio of 5:1, and the zirconium nitrate pentahydrate and the first organic ligand have a concentration of 0.1 mol / L in the first solvent. In one embodiment, the first organic ligand can be at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin. Preferably, the first organic ligand is terephthalic acid, because the zirconium-based organic framework material (UiO-66) synthesized from terephthalic acid and zirconium nitrate pentahydrate has simple preparation conditions and stable chemical properties.

[0049] In one embodiment, in this step, the reaction temperature is 80 to 120° C., and the reaction time is 10 to 48 hours.

[0050] In this step, after the reaction is completed, centrifugation, washing, drying and other treatments may also be performed to obtain the zirconium-based organic framework material.

[0051] Please continue to refer to Figure 1 , the preparation method of the iron-based bimetallic catalyst of one embodiment of the present invention is then: (S2) mixing the zirconium-based organic framework material, a second organic ligand and a metal salt in a second solvent to react and prepare a composite organic framework material. In this step, the metal salt comprises an iron salt and an active metal salt. In one embodiment, the molar ratio of the iron salt to the active metal salt is 10:1 to 1:2, which may be, for example, 10:1, 5:1, 2:1, 1:2, but is not limited thereto, and may also be any other integer or non-integer value between 10:1 and 1:2. Preferably, the molar ratio of the iron salt to the active metal salt is 10:1 or 5:1. In one embodiment, the iron salt is at least one of ferric nitrate, ferric acetate, ferric oxalate, ferric chloride and ferrous chloride, preferably, for example, ferric nitrate or ferric chloride. In one embodiment, the active metal salt is at least one of nickel nitrate, cobalt nitrate, manganese nitrate and ammonium molybdate, preferably, for example, cobalt nitrate and ammonium molybdate.

[0052] In one embodiment, the second solvent may be, for example, DMF, and the zirconium-based organic framework material and the second organic ligand have a concentration of 0.1 mol / L in the second solvent. In addition, the concentration of the metal salt in the second solvent may also be 0.1 mol / L. The second organic ligand is at least one of 2-aminoterephthalic acid, fumaric acid, and trimeric acid. Preferably, the second organic ligand is 2-aminoterephthalic acid, because the composite organic framework material (NH2-MIL-88B) synthesized from 2-aminoterephthalic acid and the metal salt has a uniform surface morphology and stable chemical properties.

[0053] In one embodiment, the mass ratio of the zirconium-based organic framework material, the second organic ligand, and the metal salt is 2.1-3.3: 0.8-1.2: 2.7-3.5, preferably 2.5-3.1: 1.0: 2.9-3.6; more preferably 3.0: 1.0: 3.5. Under this ratio, the morphology and size of the composite organic framework material formed by internal growth can ensure that it can support and wrap the zirconium-based organic framework material, thereby forming a hybrid structure.

[0054] In this step, after the mixing and reaction are completed, treatments such as centrifugation, washing, and drying may also be performed to obtain the composite organic framework material.

[0055] In one embodiment, in this step, the reaction temperature is 80 to 120° C., and the reaction time is 10 to 48 hours. Preferably, the reaction time is 15 to 30 hours, because the heating temperature and time will affect the morphology and size of MOFs, so that the final NH2-MIL-88B@UiO-66 has a regular morphology and uniform size.

[0056] Please continue to refer to Figure 1 , the preparation method of the iron-based bimetallic catalyst of one embodiment of the present invention is followed by: (S3) calcining the composite organic framework material. In this step, the calcination temperature is 400 to 900°C, and the calcination time is 1 to 10 hours. Since the calcination temperature and time will affect the morphology and particle size of the catalyst after calcination, it is preferably calcined at 450 to 600°C for 3 to 8 hours, so that the iron-based bimetallic catalyst finally loaded on ZrO2 has a regular shape and uniform particle size.

[0057] Please continue to refer to Figure 1 , the preparation method of the iron-based bimetallic catalyst of one embodiment of the present invention is then: (S4) soaking the calcined composite organic framework material in a co-metal salt solution. In this step, the co-metal salt solution is formed by dissolving a co-metal salt in deionized water. In one embodiment, the co-metal salt is at least one of sodium nitrate, sodium carbonate, sodium bicarbonate, potassium nitrate, potassium carbonate and potassium bicarbonate, and the mass ratio of the co-metal salt to deionized water is (1.1-4.1): 120; the soaking temperature is 20 to 80°C, and the soaking time is 2 to 6 hours.

[0058] Please continue to refer to Figure 1 The preparation method of the iron-based bimetallic catalyst of one embodiment of the present invention is as follows: (S5) drying the solid part of step (S4) to obtain the above-mentioned iron-based bimetallic catalyst. In one embodiment, the temperature of the drying treatment is 80 to 120° C. and the time is 7 to 9 hours.

[0059] Another embodiment of the present invention provides a method for using an iron-based bimetallic catalyst, which comprises using the iron-based bimetallic catalyst to carry out a catalytic reaction of carbon dioxide hydrogenation in a fixed bed microreactor to produce light olefins; the conditions of the catalytic reaction of carbon dioxide hydrogenation are as follows:

[0060] The temperature is 200 to 500° C., the pressure is 3 MPa, the reaction raw materials contain hydrogen / carbon dioxide in a volume ratio of 2 to 4, and the space velocity is 2000 to 15000 ml / g per hour.

[0061] Other details and conditions regarding the use of the catalyst, except for the iron-based bimetallic catalyst of the present invention, can be appropriately adjusted according to actual needs.

[0062] In order to make the iron-based bimetallic catalyst and the preparation method thereof of the present invention clearer and to verify the effect of the iron-based bimetallic catalyst in catalyzing the hydrogenation of carbon dioxide to produce light olefins, the following experiments were conducted.

[0063] Embodiment 1:

[0064] (1) Preparation of Zr-based MOFs: 1 g Zr(NO3)4·5H2O, 0.4 g H2BDC (terephthalic acid) and 15 mL formic acid were mixed evenly in 60 mL N,N-dimethylformamide (DMF), dispersed by ultrasonic treatment for 1 h, and then transferred to a polytetrafluoroethylene-lined reactor and placed in an oven and heated at 120°C for 20 h. After cooling to room temperature, the mixture was washed three times with methanol and DMF, respectively, and then centrifuged and dried in an oven at 100°C overnight to collect the white solid UiO-66.

[0065] (2) Preparation of composite MOFs: 3g UiO-66 and 1g NH2-BDC were added to 40mL DMF and mixed evenly. 3.3g Fe(NO3)3·9H2O and 0.24g Co(NO3)2·6H2O were weighed and added to 80mL DMF and mixed evenly. Then the two solutions were mixed evenly under stirring. Finally, the mixed solution was transferred to a polytetrafluoroethylene-lined reactor and heated in an oven at 100℃ for 20h. After cooling to room temperature, it was washed three times with methanol and DMF respectively, and then centrifuged and dried in an oven at 100℃ for 12h to collect the composite MOFs.

[0066] (3) Preparation of iron-based bimetallic catalyst supported on ZrO2: The composite MOFs were heated from room temperature to 500°C at a rate of 2°C / min in a muffle furnace under air atmosphere and maintained for 5 h. 0.1 g of potassium carbonate was dissolved in 10 g of deionized water to prepare a potassium carbonate aqueous solution. An equal volume of the product obtained in the muffle furnace was immersed in the potassium carbonate aqueous solution and the immersion was ultrasonicated at 60°C for 1 h. Then, the catalyst was dried at 100°C and recorded as FeCo@ZrO2.

[0067] Reference Figure 2 , presenting the X-ray diffractometer (XRD) diagram of FeCo@ZrO2. XRD characterization can preliminarily detect the material composition in the FeCo@ZrO2 catalyst. It can be seen that the composition of FeCo@ZrO2 is Fe2O3, CoFe2O4 and ZrO2.

[0068] Embodiment 2:

[0069] 2.5 g UiO-66, 2.8 g Fe(NO3)3·9H2O and 0.15 g Co(NO3)2·6H2O are used to replace 3 g UiO-66, 3.3 g Fe(NO3)3·9H2O and 0.24 g Co(NO3)2·6H2O in step (2) of Example 1, and the rest is the same as Example 1, and the obtained catalyst is recorded as FeCo@1.5ZrO2.

[0070] Reference Figure 3 The figure below shows the transmission electron microscope (TEM) image of FeCo@1.5ZrO2. The TEM characterization can observe the morphology and particle dispersion of the FeCo@1.5ZrO2 catalyst. It can be seen that the FeCo@1.5ZrO2 catalyst is mainly based on honeycomb-shaped uniform solid spheres of ZrO2, and the black metal oxides formed by Fe and Co are evenly dispersed on ZrO2.

[0071] Embodiment 3:

[0072] 2.5 g of FeCl3·9H2O was used to replace 3.3 g of Fe(NO3)3·9H2O in step (2) of Example 1. The rest of the process was the same as Example 1. The obtained catalyst was recorded as C-FeCo@ZrO2.

[0073] Embodiment 4:

[0074] 1g(NH4)6Mo7O 24 ·4H2O replaces 0.24gCo(NO3)2·6H2O in step (2) of Example 1, and the rest is the same as Example 1. The obtained catalyst is recorded as FeMo@ZrO2.

[0075] Embodiment 5:

[0076] 0.24 g of Co(NO3)2·6H2O in step (2) of Example 1 was replaced by 0.48 g of Co(NO3)2·6H2O. The rest of the steps were the same as in Example 1. The obtained catalyst was recorded as Fe2Co@ZrO2.

[0077] Embodiment 6:

[0078] The heating temperature was 80°C and the heating time was 24h instead of 100°C and 20h in step (2) of Example 1. The rest was the same as Example 1. The obtained catalyst was recorded as 80-FeCo@ZrO2.

[0079] Embodiment 7:

[0080] The calcination temperature was 600°C and the calcination time was 6 hours instead of 500°C and 5 hours in step (3) of Example 1. The rest of the steps were the same as in Example 1. The obtained catalyst was recorded as FeCo@ZrO2-600.

[0081] Embodiment 8:

[0082] 0.08 g of sodium nitrate was used to replace 0.1 g of potassium carbonate in step (3) of Example 1. The rest of the steps were the same as in Example 1. The resulting catalyst was recorded as FeCo@ZrO2-Na.

[0083] Comparative Example 1:

[0084] By replacing 3.3g Fe(NO3)3·9H2O and 0.24g Co(NO3)2·6H2O in Example 1 with 3.64g Fe(NO3)3·9H2O and the rest being the same as Example 1, a single iron-based catalyst free of a second active metal can be obtained, which is denoted as Fe@ZrO2.

[0085] Comparative Example 2:

[0086] Weigh 3.3g Fe(NO3)3·9H2O and 0.24g Co(NO3)2·6H2O and add 80mL DMF to mix evenly. Then mix the two solutions evenly under stirring. Finally, transfer the mixed solution to a polytetrafluoroethylene-lined reactor and heat it in an oven at 100℃ for 20h. After cooling to room temperature, wash it three times with methanol and DMF respectively, collect it by centrifugation, dry it in an oven at 100℃ for 12h, and collect the bimetallic MOFs. Then, MOFs are heated from room temperature to 500℃ at a rate of 2℃ / min in a muffle furnace air atmosphere and maintained for 5h. Take 0.1g potassium carbonate and dissolve it in 10g deionized water to prepare a potassium carbonate aqueous solution. Immerse an equal volume of the product obtained in the muffle furnace in the above potassium carbonate aqueous solution, and immerse it for 1h at 60℃ with ultrasound. Then, after heating and drying at 100℃, the bimetallic catalyst without ZrO2 is obtained and recorded as FeCo.

[0087] Embodiment 9:

[0088] The catalysts prepared in Examples 1-8 and Comparative Examples 1-2 were loaded into a fixed bed microreactor with an inner diameter of 8 mm. The air was purged with N2 before the reaction, and then in-situ reduced for 5 hours at a temperature of 400°C, a pressure of 0.1 MPa, and a H2 flow rate of 20 mL / min. The catalyst obtained after the reduction was used to catalyze the hydrogenation reaction of the raw gas. The reaction gas product was analyzed online using a gas chromatograph and a thermal conductivity detector (TCD).

[0089] The composition of the raw gas and the catalytic reaction conditions are as follows:

[0090] Raw gas composition: CO2: 23%, H2: 69%, N2: 8%.

[0091] Catalyst loading: 0.25 g.

[0092] Reaction temperature: 250-350℃.

[0093] Reaction pressure: 3MPa.

[0094] Reaction space velocity: 5000mL / g / h.

[0095] The CO2 conversion rate and light olefin selectivity were determined and calculated according to the following method, and the results are listed in Table 1.

[0096] CO2 conversion rate: (1-CO2 amount in the product / CO2 amount in the raw gas) × 100%

[0097] Selectivity of light olefins: (amount of CO2 converted to light olefins / amount of CO2 converted) × 100%

[0098] Table 1:

[0099]

[0100]

[0101] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, modifications and equivalent settings contained in the spirit and scope of the claims are all included in the scope of the present invention.

Claims

1. An iron-based bimetallic catalyst, characterized in that: The iron-based bimetallic catalyst comprises: an active metal; and a composite support, the composite support comprising zirconium oxide, a zirconium-based organic framework and an iron-based organic framework; in: The iron-based organic framework is coated with the zirconium-based organic framework, and The iron of the iron-based organic framework and the active metal are supported on the zirconium oxide.

2. The iron-based bimetallic catalyst according to claim 1, characterized in that: The zirconium-based organic framework comprises a first organic ligand portion, and the first organic ligand portion is selected from at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin.

3. The iron-based bimetallic catalyst according to claim 1, characterized in that: The iron-based organic framework comprises a second organic ligand part, and the second organic ligand part is selected from at least one of 2-aminoterephthalic acid, fumaric acid and trimerephthalic acid.

4. The iron-based bimetallic catalyst according to claim 1, characterized in that: The active metal is selected from at least one of cobalt, nickel, manganese and molybdenum.

5. The iron-based bimetallic catalyst according to claim 1, characterized in that: The molar ratio of iron to the active metal is 10:1 to 1:

2.

6. A method for preparing an iron-based bimetallic catalyst, characterized in that: The preparation method comprises the following steps: Step (S1): mixing zirconium nitrate pentahydrate and a first organic ligand in a first solvent to react and obtain a zirconium-based organic framework material; Step (S2): mixing the zirconium-based organic framework material, a second organic ligand and a metal salt in a second solvent, wherein the metal salt comprises an iron salt and an active metal salt, to prepare a composite organic framework material; Step (S3): calcining the composite organic framework material; Step (S4): soaking the calcined composite organic framework material in a metal salt solution; as well as Step (S5): Drying the solid portion of step (S4) to obtain the iron-based bimetallic catalyst as claimed in claim 1.

7. The method for preparing the iron-based bimetallic catalyst according to claim 6, characterized in that: The first organic ligand is selected from at least one of terephthalic acid, fumaric acid, trimerephthalic acid and tetracarboxyphenylporphyrin, and the second organic ligand is selected from at least one of 2-aminoterephthalic acid, fumaric acid and trimerephthalic acid.

8. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S1), the molar ratio of the zirconium nitrate pentahydrate to the first organic ligand is 1:

1.

9. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S1), the reaction is carried out at a temperature of 80 to 120°C and for a time of 10 to 48 hours.

10. The method for preparing the iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S2), the mass ratio of the zirconium-based organic framework material, the second organic ligand, and the metal salt is 2.1-3.3:0.8-1.2:2.7-3.

5.

11. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S2), the iron salt is selected from at least one of ferric nitrate, ferric acetate, ferric oxalate, ferric chloride and ferrous chloride; and the active metal salt is selected from at least one of nickel nitrate, cobalt nitrate, manganese nitrate and ammonium molybdate.

12. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S2), the molar ratio of the iron salt to the active metal salt is 10:1 to 1:

2.

13. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S3), the calcination is performed at a temperature of 400 to 900°C and for a time of 1 to 10 hours.

14. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In step (S4), the auxiliary metal salt solution is formed by dissolving an auxiliary metal salt in deionized water, wherein the auxiliary metal salt is selected from at least one of sodium nitrate, sodium carbonate, sodium bicarbonate, potassium nitrate, potassium carbonate and potassium bicarbonate, and the mass ratio of the auxiliary metal salt to deionized water is (1.1-4.1):120; the soaking temperature is 20 to 80°C, and the soaking time is 2 to 6 hours.

15. The method for preparing an iron-based bimetallic catalyst according to claim 6, characterized in that: In the step (S5), the drying process is carried out at a temperature of 80 to 120°C and for a time of 7 to 9 hours.

16. A method for using an iron-based bimetallic catalyst, characterized in that: The iron-based bimetallic catalyst as claimed in claim 1 is used to carry out a catalytic reaction of carbon dioxide hydrogenation in a fixed bed microreactor to produce light olefins; the conditions of the catalytic reaction of carbon dioxide hydrogenation are as follows: The temperature is 200 to 500° C., the pressure is 3 MPa, the reaction raw materials contain hydrogen / carbon dioxide in a volume ratio of 2 to 4, and the space velocity is 2000 to 15000 ml / g per hour.

Citation Information

Patent Citations

  • Catalyst for preparing high-carbon alpha-olefin by hydrogenation of carbon dioxide, and preparation method and application

    CN109675573A

  • Method for synthesizing low-carbon olefin through carbon dioxide hydrogenation by adopting iron-based catalyst

    CN112169799A

  • Iron-cobalt catalyst suitable for catalyzing hydrogenation reaction of carbon dioxide as well as preparation method and application of iron-cobalt catalyst

    CN117563640A

  • NH2-MIL-53 / UiO-66-NH2 catalyst for photocatalytic reduction of CO2 as well as preparation method and application of NH2-MIL-53 / UiO-66-NH2 catalyst

    CN117643921A

  • Method for manufacturing composite catalyst of porous metal complex and inorganic catalyst material

    JP2013198844A

Cited By

  • Zirconium-based double-active-center catalyst as well as preparation method and application thereof

    CN120209185A

  • A zirconium-based double-active-center catalyst and its preparation method and application

    CN120209185B